2002
DOI: 10.1055/s-0038-1634388
|View full text |Cite
|
Sign up to set email alerts
|

The Index as a New Concept towards an Integrated Framework for the Electronic Patient Record

Abstract: Summary Objective: To overcome some classical limitations of the POMR (Problem-Oriented Medical Record), including the management of divergent opinions between health professionals, in order to construct a common patient record across multiple disciplines in hospital settings and professional networks. Methods: Using a complex clinical case, we improved a POMR model previously used by GPs in order to translate it into a hospital setting. The enhanced model has been assessed through use in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In looking, as an example, at recent publicationsinthis journal, we can see how intensivelymedical text processing andthe electronic patientr ecord have become part of medical informaticsr esearch andp ractise. Approximately40yearsafterWolfgang Giere's firstp ublications, we can now read publicationsonfunctionality andarchitecture [34][35][36][37][38][39][40][41][42][43][44][45], on organizationali ssues [46][47][48][49], on evaluation [50][51][52][53][54], andontechnicalissues [55,56] of medical texts andpatient records.The electronic patientr ecord hasbecome an importantcomponent for cooperative,sharedcare [57][58][59][60]. It becamea relevant part of educational programs [ 61] ande venatopic of ethicald iscussion [62,63].…”
Section: Electronicpatient Informationmentioning
confidence: 99%
“…In looking, as an example, at recent publicationsinthis journal, we can see how intensivelymedical text processing andthe electronic patientr ecord have become part of medical informaticsr esearch andp ractise. Approximately40yearsafterWolfgang Giere's firstp ublications, we can now read publicationsonfunctionality andarchitecture [34][35][36][37][38][39][40][41][42][43][44][45], on organizationali ssues [46][47][48][49], on evaluation [50][51][52][53][54], andontechnicalissues [55,56] of medical texts andpatient records.The electronic patientr ecord hasbecome an importantcomponent for cooperative,sharedcare [57][58][59][60]. It becamea relevant part of educational programs [ 61] ande venatopic of ethicald iscussion [62,63].…”
Section: Electronicpatient Informationmentioning
confidence: 99%
“…Salmon et al listed some limitations of the POMR, but also suggested some areas in which it may be extended [11]. De Clercq suggested a flexible link between data and problems to extend the POMR architecture [12]. The Institute of Medicine report recommends that an EHR should contain a problem list from which clinicians can easily obtain a concise view of all of a patient's medical problems [13].…”
Section: Introductionmentioning
confidence: 99%